Look Beyond the Brain: A Case of Insulinomatosis Disguised as Frontal Lobe Epilepsy and Review of the Literature - Somaya Albalawi¹; Suha O. Alzubaidy²; Shatha H. Al Kenani²; Batool S. Bedaiwi³; Rimas A. Alqarni³; Mohammed A. Alhowaish⁴; Israa A. Alhawaj⁵; Abdulbasit M. Bugis⁶ (DawnMed Journal of Medical Science, 2026)
Background: Insulinomatosis is a rare and underrecognized cause of endogenous hyperinsulinemic hypoglycemia (EHH) defined by multicentric insulinsecreting pancreatic neuroendocrine tumors (PanNETs) accompanied by diffuse neuroendocrine microadenomatosis. Neuroglycopenic manifestations of hypoglycemia frequently mimic primary neurological and psychiatric disorders, leading to substantial diagnostic delays that adversely affect patient outcomes.Case Presentation: We report a 32-year-old woman who carried a diagnosis of refractory frontal lobe epilepsy for approximately one year before the true etiology was identified. Her recurrent episodes of hypermotor activity, emotional lability, and facial twitching had been attributed to frontal lobe seizures and managed with escalating doses of lamotrigine. The pivotal diagnostic clue emerged when a seizure was documented in association with hypoglycemia (glucose 40–50 mg/dL; 2.2–2.8 mmol/L), prompting continuous glucose monitoring that confirmed recurrent hypoglycemic episodes. A supervised 72-hour fasting test established endogenous hyperinsulinemic hypoglycemia, with inappropriately elevated insulin (66 pmol/L), C-peptide (0.90 nmol/L), and markedly elevated proinsulin (36.01 pmol/L). Contrast-enhanced computed tomography and endoscopic ultrasound identified a dominant lesion in the pancreatic head; however, Ga-68 DOTATATE positron emission tomography/computed tomography (PET/CT) revealed at least four somatostatin receptor–avid lesions distributed across the head, body, and tail of the pancreas. The patient underwent A Whipple procedure (pancreaticoduodenectomy) with enucleation and resection of additional pancreatic lesions. Final histopathology demonstrated multiple well-differentiated PanNETs of variable sizes with neuroendocrine microadenomatosis throughout the pancreatic parenchyma, consistent with insulinomatosis. Multiple endocrine neoplasia type 1 (MEN1) was excluded on biochemical screening. Postoperatively, hypoglycemia resolved completely and antiseizure medication was discontinued.Conclusion: This case underscores the critical importance of excluding hypoglycemia in patients presenting with atypical or drug-resistant seizures and highlights insulinomatosis as a rare yet clinically significant differential diagnosis. Early recognition of Whipple's triad, coupled with the strategic use of functional imaging such as Ga-68 DOTATATE PET/CT, is essential for guiding timely and definitive surgical management to achieve biochemical cure.
Keywords: Insulinomatosis, endogenous hyperinsulinemic hypoglycemia, pancreatic neuroendocrine tumor, frontal lobe epilepsy, neuroglycopenia